Baals of Bashan - Miller, Robert D. 1966-2023 (2014)
This essay argues that the phrase 'Bulls of Bashan' is not about famous cattle but about cultic practice. Although this has been suggested before, this essay uses archaeology and climatology to show ancient Golan was no place for raising cattle.\n4207 Cet essai fait valoir que l’expression «Taureaux de Basan» ne concerne pas les célèbres bovins mais des pratiques rituelles. Bien que cela ait été suggéré auparavant, cet essai utilise archéologie et climatologie pour montrer que le Golan antique n’était pas un endroit pour l’élevage du bétail.\n4207 \n4207